Effects of different maturity status on change of direction performance of youth tennis players - Jaime Fernandez-Fernandez; Jose Canós-Portalés; Rafael Martínez-Gallego; Francisco Corbi; Ernest Baiget (Termedia Publishing House, 2022)
The aim of this study was to examine the maturational status (i.e., peak height velocity [PHV]) differences in neuromuscular performance (i.e., vertical jump, linear sprint, change of direction (COD) using different tests, and change of direction deficit [CODD]) of young tennis players. One hundred and two tennis players (70 boys and 52 girls; age 13.9± 2.0 years, body mass 53.3± 12.7 kg, height 163.1± 11.9 cm) participated in the study and were divided into Pre-PHV (n = 26), Circa-PHV (n = 33) and Post-PHV (n = 43) groups. Testing included speed (5, 10, and 20 m), COD tests (i.e., modified 5-0-5, pro-agility and hexagon), and bilateral/unilateral countermovement jump (CMJ). Pre- and Circa-PHV players presented lower levels of performance in jumping ability (i.e., both bilateral and unilateral CMJs; P < 0.001; ES: 0.85 to 0.98), linear sprints (5 to 20 m; P < 0.05 to < 0.001; ES: 0.67 to 1.19) and COD ability tests (modified 5-0-5 test, pro agility and hexagon) compared to the Post-PHV players. Moreover, Pre-PHV players presented lower CODD% (p < 0.05; ES: 0.68-0.72) than Post-PHV for both forehand and backhand sides, and Circa-PHV showed lower values in the CODD of the rolling situation to the forehand side (p < 0.05; ES: 0.58). Among the COD tests, the pro-agility test seems to be a simple, easy-to-implement and reliable test, which can provide interesting information about the COD with higher entry speeds. Moreover, specific training strategies related to the PHV and focused not only on the neuromuscular training and COD workouts, but also on maximizing motor skill proficiency, should be recommended.